Intercropping gardenpea (Pisium sativum) with Maize (Zea mays) at farmers’ field - Khan, MAH; Sultana, N; Akter, N; Zaman, MS; Islam, MR (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted at the farmers’ field of Phulpur MLT site of On- Farm Research Division, Bangladesh Agricultural Research Institute (BARI), Mymensingh during 2015-16 and 2016-17 to find out a suitable intercrop combination of garden pea with maize for higher productivity and profitability. Five treatments, viz. T1= Maize (100%) + one row garden pea (33%) in between maize lines, T2= Maize (100%) + two row garden pea (66%) in between maize lines, T3= Maize (100%) + garden pea broadcast (100%) in between maize lines, T4= Sole maize and T5= Sole garden pea were tested following RCB design with six dispersed replications. Maize var. BARI Hybrid Maize-9 and garden pea var. BARI Motorshuti-3 were used in monoculture as well as in intercropping situations. Intercropping of garden pea improved the yield components of maize and offered some additional yield. The highest maize grain yield (8.62 t ha-1) and maize equivalent yield (20.22 t ha-1 yr-1) were recorded with maize (100 %) + two rows of garden pea (66 %) in between maize lines (T2). The values of all the competition functions were greater than unity and maize (100 %)+ two rows of garden pea (66 %) in between maize lines (T2) showed higher values of land equivalent ratio (1.56), gross return (Tk. 311920 ha-1), gross margin (Tk. 175697 ha-1) and BCR (2.29) as compared to other treatments. Bangladesh J. Agril. Res. 43(4): 691-702, December 2018